STRENGTHENING TEACHERS' UNDERSTANDING OF RELIGIOUS MODERATION AT MTsN 1 PIDIE JAYA - RAHMAWATI, RAHMAWATI (MSJ : Majority Science Journal, 2025)
This study arises from the context of implementing Sharia Law in Aceh, which necessitates strengthening religious moderation to foster tolerance and respect for diversity. The research focuses on teachers' understanding of religious moderation at MTsN 1 Pidie Jaya, the factors influencing it, and the strategies employed for its reinforcement. Data were collected through interviews, observations, and documentation involving the head of the madrasah, the deputy head, and several teachers. The findings indicate that teachers have a reasonably good understanding of religious moderation, supported by internal factors. and external factors leadership support, training, modules, and online seminars. Challenges encountered include time constraints, limited access to relevant literature, and the socio-cultural homogeneity in Pidie Jaya. Reinforcement efforts include regular training, provision of relevant teaching materials, collaboration with religious figures, group discussions among teachers, and the use of social media. These strategies are considered effective but require ongoing evaluation and material development to ensure comprehensive implementation of religious moderation.